PENGARUH MENGGAMBAR OUTDOOR TERHADAP PERKEMBANGAN VISUAL SPASIAL ANAK KELOMPOK B DI RA AL FATTAH WAJAK-MALANG - Munawaroh , Anik; Sholichah, Norma Ita (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2023)
The outdoor drawing learning is one of the strategies to build a learning atmosphere so that children are free to express themselves. The research objectives included the development of children's spatial visual intelligence, outdoor and indoor learning, and the effect of outdoor drawing learning on visual spatial intelligence in group B children at RA Al-Fattah Wajak. The research method focuses on quantitative research with a pre-experimental research design in the form of one-group, pretest-posttest design. The results of the research seen through the Pre Test and Post Test data showed a very significant change between the X results with a percentage of 0.7%, while Y with a percentage of 40.8%. Meanwhile, the comparison between learning needs through indoor and outdoor between X results with a percentage of 4.9%, while Y learning outcomes with a percentage of 52.9%. The qualitative results show that learning to draw outdoors using the play method and field trips affects spatial visual intelligence in four aspects. The research suggestion lies in the achievement results which can be improved according to the aspect indicators that are more extended, with more interesting learning innovations.